Bis(tercarbazole) pyrene and tetrahydropyrene derivatives: photophysical and electrochemical properties, theoretical modeling, and OLEDs. Issue 17 (8th April 2019) - Kaafarani, Bilal R.; El-Assaad, Tarek H.; Smith, William A.; Ryno, Sean M.; Hermerschmidt, Felix; Lyons, Jeffrey; Patra, Digambara; Wex, Brigitte; List-Kratochvil, Emil J. W.; Risko, Chad; Barlow, Stephen; Marder, Seth R.
Abstract : The title compounds are compared to bis(carbazole) analogues. They exhibit multiple oxidations, dual fluorescence (in one case), and function as emissive layers in OLEDs. Abstract : 2, 7-Bis(3, 3′′, 6, 6′′-tetra( tert -butyl)-9′ H -9, 3′:6′, 9′′-tercarbazol-9-yl)-4, 5, 9, 10-tetrahydropyrene (3 ) and 2, 7-bis(3, 3′′, 6, 6′′-tetra( tert -butyl)-9′ H -9, 3′:6′, 9′′-tercarbazol-9-yl)pyrene (4 ), along with a model compound, 3, 3′′, 6, 6′′-tetra( tert -butyl)-9′-(4-( tert -butyl)phenyl)-9′ H -9, 3′:6′, 9′′-tercarbazole (6 ), have been synthesized using microwave-assisted palladium-catalyzed coupling and compared to analogous 3, 6-di( tert -butyl)carbazol-9-yl species (1, 2, and5 ). Time-dependent density functional theory (TDDFT) calculations reveal absorption with quadrupolar (ter)carbazole-to-bridge CT character for1–4 . Compound4 is unusual in showing dual fluorescence in a number of solvents; the longer wavelength feature of which is markedly more solvatochromic than the bands of the other compounds. Following the observed three oxidations on the TCz model compound6, compounds3 and4 can be electrochemically reversibly oxidized to hexacations with four oxidation and three oxidation steps in a 2 : 2 : 1 : 1 and a 2 : 2 : 2 current ratio, respectively. Tercarbazole derivatives3 and4 have been used as the emissive layers of simple solution-processed few-layer organic light-emitting diodes.